A comparison of the clinical effects of arthroscopic treatment for popliteal cyst between techniques using one posteromedial portal and two posteromedial portals. Issue 20 (15th May 2020) - Guo, Dongsheng; Cheng, Liang; Chen, Guangxiang; Yu, Xiao; Zhang, Hong; She, Yuanshi
Abstract : Abstract: There is a lack of research comparing the clinical effects of arthroscopic treatment of popliteal cysts between the one posteromedial portal (OPP) technique and the two posteromedial portals (TPP) technique. The aim of this study was to evaluate and compare the clinical efficacy of arthroscopic treatment for popliteal cysts between the 2 techniques. Patients with symptomatic popliteal cysts after surgery were retrospectively invited to participate in this study. They received arthroscopy treatment via the OPP technique or the TPP technique. At the final follow-up, the Rauschning and Lindgren criteria and the Lysholm score were used for clinical evaluation. Moreover, magnetic resonance imaging was performed to detect the recurrence of cysts postoperatively. Finally, 53 patients with symptomatic popliteal cysts were included in this study, including 25 in the OPP group and 28 in the TPP group. The operation time of the TPP group was significantly longer than that of the OPP group ( P < .001). In the OPP group, the cysts disappeared in 17 patients and reduced in size in 8 patients. In the TPP group, the cysts disappeared in 23 patients and reduced in size in 5 patients. According to the Rauschning and Lindgren classification, the recurrence rate was significantly lower in the TPP group (0%) than in the OPP group (4%) ( P = .03). In addition, there was no significant difference in the Lysholm score between the OPP group and the TPP group ( P = .77). TPP technique is more effective and superior than OPP technique for the treatment of popliteal cysts.